1987
DOI: 10.1038/icb.1987.60
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgA antibody response in Ross River virus infection

Abstract: Summary. Sera were collected over a period of several years from the onset of initial symptoms from 77 patients with Ross River virus infection. When tested for virus-specific IgA antibodies, using an enzymelinked immunosorbent assay {ELISA) based on antibody class capture, 245 out of 704 sera were antibodypositive. Although Ross River virus IgA antibodies were present in the serum of all patients soon after onset of symptoms, the IgA response was relatively short-lived in comparison with specific IgM antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…38,[119][120][121][122][123] The most prominent changes linked to aging are the deterioration of different components of adaptive immunity. [124][125][126][127] As adaptive immunity and antibody responses are important in the resolution of alphavirus infection, 95,[128][129][130] the deterioration of adaptive immunity in the elderly would potentially lead to more severe pathology and chronic complications. Indeed, when a cohort study was performed on CHIKV-infected patients from the 2006-2007 R eunion Island outbreak, 78% of the patients with chronic arthralgia were elderly (> 60 years old).…”
Section: Changes In Adaptive Immunity With Agementioning
confidence: 99%
“…38,[119][120][121][122][123] The most prominent changes linked to aging are the deterioration of different components of adaptive immunity. [124][125][126][127] As adaptive immunity and antibody responses are important in the resolution of alphavirus infection, 95,[128][129][130] the deterioration of adaptive immunity in the elderly would potentially lead to more severe pathology and chronic complications. Indeed, when a cohort study was performed on CHIKV-infected patients from the 2006-2007 R eunion Island outbreak, 78% of the patients with chronic arthralgia were elderly (> 60 years old).…”
Section: Changes In Adaptive Immunity With Agementioning
confidence: 99%
“…Our results showed that both IgA and IgG anti-SARS-CoV-2 were already present in the first collected serum sample, 20 days after the onset of the symptoms. As with other viral infections (37,38), the detection of serum IgA antibodies was limited in time, while the presence of IgG antibodies could be identified in the serum for long periods and present during the entire period of the study. Additionally, from the beginning of the sera collection, we identified the presence of total neutralizing antibodies (which can be of all immunoglobulin classes), with fluctuations during sampling.…”
Section: Discussionmentioning
confidence: 83%
“…BFV diagnosis is confirmed by a virus-specific-IgM response (Cashman et al, 2008 (Carter et al, 1987). Viral culture and polymerase chain reaction (PCR) are less widely used diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%